Unknown cold-tolerant Clostridium spp.: Characteristics and potential to cause meat spoilage. (April 2022) - Dorn-In, Samart; Mang, Sirkka; Schwaiger, Karin
Abstract: Clostridium spp. are ubiquitous bacteria and often found in foods and animals. Some species are pathogenic, others food spoiling or commensals. In this study, 65 cold-tolerant Clostridium spp. strains isolated from variable samples (beef, lamb, venison, feces/skin of wild boars) were investigated. Fifty strains were lecithinase positive; six additionally produced β -hemolysis. By applying specific qPCR, 16S rRNA gene analysis, RFLP method, and MALDI-TOF MS, they were classified into two major groups: 29 strains were identified as C. tagluense -like, while the other 36 remained unidentified. Subsequently, twenty-two vacuum-packed beef samples were spiked with a single strain from both groups and stored at 4 °C for 8 weeks. The odor of challenged samples was variable (from unchanged, sour/musty, to sulfurous), while color, meat consistency and drip loss were similar to the control group. The ability to produce gas of all tested strains was lower than of C. estertheticum . Even though both groups of cold-tolerant clostridia exhibited similar 16S rRNA genes and biochemical activities, RFLP methods and MALDI-TOF MS are sufficient to differentiate them. In terms of food safety, strains producing lecithinase and hemolysin should be further investigated for their potential to produce substances affecting human and animal health. Highlights: 65 cold-tolerant clostridia were isolated from fresh meat, feces and animal skin. 50 strains produced lecithinase, 6 strains additionally produced β -hemolysin. 29 strains were identified as C. tagluense -like, while 36 strains remained unknown. RFLP and MALDI-TOF MS but not the 16S rRNA gene can differentiate both groups. 22 strains could spoil chilled vacuum-packed beef accompanied by low gas production.